Grounded Theory methodological aspects in Brazilian nursing thesis - Girardon-Perlini,Nara Marilene Oliveira (2020)
ABSTRACT Objective: to analyze the application of methodological aspects of Grounded Theory in Brazilian nursing thesis. Methods: qualitative, descriptive study elaborated based on theses available in the CAPES Thesis and Dissertations Catalog, located with the search for the terms “Teoria Fundamentada nos Dados” OR “Grounded Theory”, from 2013 to 2017. The data obtained were analyzed, considering the Grounded Theory methodological assumptions. Results: observance of Grounded Theory basic concepts and articulation with several theoretical frameworks in the conduct of the investigations are strengthening aspects of the method. However, dissent in the description of the operationalization of the stages and naming of the elaborated construct weaken the methodological quality. Final considerations: the methodological consistency provided by Grounded Theory has the potential to demonstrate the studies’ rigor and reliability conducted and theories generated. It is necessary to deepen theoretical-conceptual studies to elucidate discrepancies in the applicability in nursing research.